Maximum Power Point Tracking of PV Grids Using Deep Learning - K. Rafeeq Ahmed; Farrukh Sayeed; K. Logavani; T. J. Catherine; Shimpy Ralhan; Mahesh Singh; R. Thandaiah Prabu; B. Bala Subramanian; Adane Kassa (International Journal of Photoenergy, 2022)
In this paper, we develop a deep learning model using back propagation neural network (BPNN) that helps to obtain maximum power point. This deep learning model aims to maximise the output power from the solar grids when the panels are connected with the boost converter under different variable load conditions. BPNN-DL enables the prediction of reference voltage at different weather conditions for severing the various output power that ensures maximum power with stable output voltage. The proposed BPNN-DL is tested under different conditions to estimate the robustness of the modules under internal/external interferences. The results of the simulation show that the proposed method achieves maximum output power from each panel compared with existing methods in terms of regression analysis on training, testing, and validation.